Expert Council: promising areas of systemic enzyme therapy in gynecology - Yu.E. Dobrokhotova; A.A. Khryanin; E.V. Shikh; L.Yu. Karakhalis; I.M. Ordiyants; Kogan E.A; A.V. Yakimova; I.N. Korotkikh; N.I. Kokhno (LCC «Medicine-Inform», 2023)
Yu.E. Dobrokhotova1, A.A. Khryanin2, E.V. Shikh3, L.Yu. Karakhalis4, I.M. Ordiyants5, E.A. Kogan1, A.V. Yakimova2, I.N. Korotkikh6, N.I. Kokhno7 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Novosibirsk State Medical University, Novosibirsk, Russian Federation 3I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation 4Russian University of Peoples' Friendship, Moscow, Russian Federation 5Kuban State Medical University, Krasnodar, Russian Federation 6N.N. Burdenko Voronezh State Medical University, Voronezh, Russian Federation 7LLC "Center of Reproduction and Genetics", Moscow, Russian Federation The interdisciplinary scientific and practical conference «Expert Council: promising areas of systemic enzyme therapy (SET) in gynecology» under the auspices of the National Association of Obstetricians-Gynecologists and Reproductologists "Women's Health" was held in Moscow on December 02, 2022. The conference brought together specialists from multiple Russian regions. The development of effective treatment algorithms for infection-caused inflammatory diseases in the practices of obstetricians and gynecologists remains relevant in view of the continuous growth of antimicrobial resistance underpinned both by the irrational use of antibiotics and the biofilm-forming ability of infectious agents. The speakers shared their experience of using systemic enzyme therapy (SET) in the combination treatment of inflammatory diseases in obstetric and gynecological practice, as well as in the prevention of fibrous and adhesive complications of pelvic inflammatory diseases (PID) and gynecologic surgeries. It was pointed out that systemic enzyme therapy should be recognized as a justified component of the combination PID treatment which helps to reduce the duration and severity of symptoms due to its proven immunomodulatory, fibrinolytic and antiplatelet effects. The use of SET drugs reduces the duration of all stages of reparative regeneration along with tamping down the inflammatory response. The Expert Council Resolution provides recommendations on using SET in gynecology. Keywords: proteolytic enzymes, pelvic inflammatory diseases, endometritis, adhesions, antibiotic resistance, systemic enzyme therapy. For citation: Dobrokhotova Yu.E., Khryanin A.A., Shikh E.V. et al. Expert Council: promising areas of systemic enzyme therapy in gynecology. Russian Journal of Woman and Child Health. 2023;6(2):149-156 (in Russ.). DOI: 10.32364/2618-8430-2023-6-2-149-156.